Molecular allergen profiling in horses by microarray reveals Fag e 2 from buckwheat as a frequent sensitizer. Issue 7 (27th February 2018) - Einhorn, L.; Hofstetter, G.; Brandt, S.; Hainisch, E. K.; Fukuda, I.; Kusano, K.; Scheynius, A.; Mittermann, I.; Resch‐Marat, Y.; Vrtala, S.; Valenta, R.; Marti, E.; et al.
Abstract: Background: Companion animals are also affected by IgE‐mediated allergies, but the eliciting molecules are largely unknown. We aimed at refining an allergen microarray to explore sensitization in horses and compare it to the human IgE reactivity profiles. Methods: Custom‐designed allergen microarray was produced on the basis of the ImmunoCAP ISAC technology containing 131 allergens. Sera from 51 horses derived from Europe or Japan were tested for specific IgE reactivity. The included horse patients were diagnosed for eczema due to insect bite hypersensitivity, chronic coughing, recurrent airway obstruction and urticaria or were clinically asymptomatic. Results: Horses showed individual IgE‐binding patterns irrespective of their health status, indicating sensitization. In contrast to European and Japanese human sensitization patterns, frequently recognized allergens were Aln g 1 from alder and Cyn d 1 from Bermuda grass, likely due to specific respiratory exposure around paddocks and near the ground. The most prevalent allergen for 72.5% of the tested horses (37/51) was the 2S‐albumin Fag e 2 from buckwheat, which recently gained importance not only in human but also in horse diet. Conclusion: In line with the One Health concept, covering human health, animal health and environmental health, allergen microarrays provide novel information on the allergen sensitization patterns of the companion animals around us, which may form a basis for allergen‐specific preventive and therapeutic concepts.